ʿUmar ibn al-Khaṭṭāb’s Encounter with an Unnamed Monk: From History to Legend - Ibrahim Zein (14620036) (2023)
The Ambrosian Library in Milan has preserved thirteen very interesting folios written in an archaic semi-Kūfī Arabic script, describing an encounter between the second caliph of Islam ʿUmar ibn al-Khaṭṭāb and an unnamed monk. We demonstrate how the anonymous author of this manuscript was familiar with the ṣulḥ agreements, the covenants of the Prophet Muḥammad, and historical and anecdotal accounts of encounters between ʿUmar and ecclesiastical authorities. We postulate that our author composed his narrative on the basis of his own historical imagination from sources that probably belonged to monastic archives to which he had access. The author aimed to deliver a subtle political message, highlighting the archetypal relationship between a Muslim ruler and a Christian subject living under Islam. Two adaptations of our text have been found in Islamic sources, the first in al-Khaṭīb al-Baghdādī’s Al-zuhd wa- al-raqāʾiq, and the second in Ibn ʿAsākir’s Tārīkh madīnat Dimashq, which we argue reflect a later re-working of the original narrative. Other Information Published in: Islam and Christian–Muslim Relations License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09596410.2023.2229615